FEDERAL ACTIVITIES (Tufts Archival Research Center, 2007)
Outline of Tobacco Institute (TI) Federal Relations 1980 departmental goals and objectives. Aims to increase access to congressional officers, improve working relations with tobacco industry organizations, and strengthen their relationship with the Executive Branch, the White House, and departments and agencies, as well as develop coalitions with non-tobacco Congressional staff and improve TI political effectiveness. Lists primary issues, major projects, and legislation.